JENIS HIJAUAN PAKAN DAN KECUKUPAN NUTRIEN KAMBING JAWARANDU DI KABUPATEN BREBES JAWA TENGAH - Purbowati, Endang; Rahmawati, Ikha; Rianto, Edy (Pastura, 2015)
A survey study was carried out to investigate the kinds of forage and nutrient adequacy of Jawarandu goats in Brebes Regency, Central Java Province. The study was conducted in three sub-districts Tonjong, Bumiayu, and Paguyangan, involving 504 Jawarandu goats belonging to 45 farmers. Determination of the location, farmers and goat as samples was done by purposive sampling method. The results showed that feedstuffs of Jawarandu goat in Brebes Regency were Albasia (Albaziafalcataria), Mahogany (Swietenia mahogany), Suren (Toonasureni), Kaliandra (Calliandrahaematocephala), and Gamal (Glyricidiasepium). Nutrients consumed by Jawarandu goat in BrebesRgency exceeded the needs as recommended by Kearl (1982). It suggested that Jawarandu goat farmers in Brebes Regency be given counseling/training on feeding management for feed utilization being more efficient. Key words: forage, Jawarandu goat, nutrient adequacy